THE BOUNDS TEST TO THE LEVEL RELATIONSHIP AND CAUSALITY BETWEEN FOREIGN DIRECT INVESTMENT AND INTERNATIONAL TOURISM: THE CASE OF TURKEY - Katircioglu, Salih (Technicka Univ & Liberci, 2011)
Research on searching the empirical relationship between international tourism and foreign direct investment (FDI) is quite rare in the relevant literature. [16] find that FDI is a catalyst for international tourism in the case of China. However, more empirical works are needed in the literature; therefore, this paper contributes to this literature by empirically investigating the level relationship and the direction of causality between the net FDI inflows and international tourism in a developing economy, Turkey. The present study employs the bounds test for long run equilibrium relationship as developed by [12] and Granger causality tests under vector error correction modeling with that respect. Results suggest that both variables are in long-run equilibrium relationship only when FDI is dependent variable under the ARDL (auto-regressive distributed lag) modeling approach. Results did not reveal any long run equilibrium relationship amongst these variables when international tourism variable is dependent in the bounds test of [12]. Final investigation in the present study is that international tourist arrivals to Turkey stimulates an expansion in the net FDI inflows. Thus, in opposite to the findings of [16], the results of the present study reveal that international tourism is a catalyst for foreign direct investment in the long run of the Turkish economy. The present study implicates that the Turkish authorities should promote international tourism since both its economy and foreign based investments will be positively inluenced from the development of this foreign exchange earning sector. This study shows that there is a huge need for further attention for this debate from the other researchers.
Keywords: FDI; International Tourism; Bounds Test; Turkey